The contest of queerbaiting: Negotiating authenticity in fan–creator interactions. (1st June 2018) - McDermott, Michael
Queerbaiting emerged as a named phenomenon through fan communities challenging the purportedly intentional exploitation of their queer sensibilities and desires. Analysing how this dynamic is staged through fan–creator interactions is paramount to understanding queerbaiting. I suggest that ownership over and claim of a single, authentic textual meaning and story is at the heart of the contest of queerbaiting. I employ fans and creators of the television shows Supernatural and Teen Wolf as case studies and analyse their interactions in online videos of fan conventions. I argue that the authenticity and commitment to a supposedly singular meaning is negotiated in these interactions through the humorous sexualization of the actors and characters. My central argument is that fan–creator contestations demonstrate that accusations of queerbaiting ultimately rely on notions of authorial intention and control.